2022
DOI: 10.1111/mms.12913
|View full text |Cite
|
Sign up to set email alerts
|

The effect of commercial and artisanal fishing practices on the behavioral budget of bottlenose dolphins off the coast of Montenegro, South Adriatic Sea

Abstract: The spatial–temporal distribution of cetacean species often overlaps with fishing practices in the Mediterranean, having direct and indirect consequences. This is the first long‐term study focusing on the effects of fisheries on the behavior of T. truncatus in Montenegro. Focal group scan sampling was used during surveys between September 2016 and August 2020 to create transition probability matrices using first‐order Markov chains for behavioral states in both control (absence of fishery practices) and impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The behaviour did not appear to be influenced by time of day, but surface feeding and socializing increased in autumn and winter, suggesting seasonal variability (Affinito et al, 2019). A longer study -2020Rudd et al, 2022) based on observations from boats and from land in the same area confirmed that travelling and diving accounted for the majority of observed behaviour, respectively 43% and 33%, while socializing accounted for 10%, surface feeding 7%, and approaches to boats 4%. Socializing was reportedly higher in summer and autumn, while surface feeding was predominant in winter (Rudd et al, 2022).…”
Section: Behaviourmentioning
confidence: 83%
See 1 more Smart Citation
“…The behaviour did not appear to be influenced by time of day, but surface feeding and socializing increased in autumn and winter, suggesting seasonal variability (Affinito et al, 2019). A longer study -2020Rudd et al, 2022) based on observations from boats and from land in the same area confirmed that travelling and diving accounted for the majority of observed behaviour, respectively 43% and 33%, while socializing accounted for 10%, surface feeding 7%, and approaches to boats 4%. Socializing was reportedly higher in summer and autumn, while surface feeding was predominant in winter (Rudd et al, 2022).…”
Section: Behaviourmentioning
confidence: 83%
“…A longer study -2020Rudd et al, 2022) based on observations from boats and from land in the same area confirmed that travelling and diving accounted for the majority of observed behaviour, respectively 43% and 33%, while socializing accounted for 10%, surface feeding 7%, and approaches to boats 4%. Socializing was reportedly higher in summer and autumn, while surface feeding was predominant in winter (Rudd et al, 2022). In a different study conducted from boats, the most frequent behaviour recorded at the beginning of each sighting was diving (57%), followed by the active following of a trawler (24%), while the remaining 19% included dive-travelling, travelling and resting (Miočić-Stošić et al, 2020).…”
Section: Behaviourmentioning
confidence: 83%
“…It is important to understand the role of harmonics, specifically considering their high occurrence in each location during the current study. Although this study focuses on geographical differences of whistle variables between study locations, previous studies indicated that 50% of focal bottlenose dolphin groups in Montenegro were observed with the presence of subadults, with dolphins spending 70% of their time travelling, while milling and socialising behaviour only formed 10% or less of the total behavioural budget (Clarkson et al, 2020;Akkaya et al, 2021;Rudd et al, 2022). Above all, both of the locations have a significant amount of marine traffic; with approximately 4,130 vessels in the port of Taranto per year (Shipnext.com).…”
Section: Discussionmentioning
confidence: 99%
“…Marine mammals, a sentinel group of marine megafauna, are threatened by a plethora of anthropogenic activities, such as chemical and noise pollution, resource depletion, habitat modification/loss, vessel collisions and fishing activities (Baulch & Perry, 2014; Lauriano et al ., 2014; Merchant et al ., 2014; Knowlton et al ., 2016; Alexiadou et al ., 2019; Bernaldo De Quirós et al ., 2019; Rudd et al ., 2022). In particular, interactions between fisheries and marine mammals usually stem from depredation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the central and eastern parts of the Mediterranean Sea are largely oligotrophic, they host most marine mammal species found in this region. Until recently, the research output regarding the impacts of fisheries on local marine mammal populations originating from these areas was limited (IUCN, 2012), however in more recent years a few studies have addressed marine mammal-fisheries interactions in the region (Snape et al ., 2018; Karamanlidis et al ., 2020; Rudd et al ., 2022). In addition to that, interactions between bottlenose dolphins ( Tursiops truncatus Montagu, 1821; hereafter termed bottlenose dolphins) and SSF have been reported from coastal areas of Sardinia, Italy (Díaz López, 2006; Díaz López & Bernal Shirai, 2007; Pennino et al ., 2016), the Balearic Islands, Spain (Brotons et al ., 2008; Gazo et al ., 2008) and western Greece (Gonzalvo et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%